Engaging Employees through High Performance Work Practices: Case Studies from Higher Educational Institutions - Mohamed, Rosmah; Mohamad, Wardah; Abdullah, Haslinda (International Journal of Engineering and Technology, 2018)
Human resource management plays an important role in an organization. In recent years, scholars have devoted a great deal of attention to investigating the relationship between high performance work practices and organizational performance. There have been numerous studies focused on empirically examining the impact of high performance work practices on performance outcomes. These studies suggest that there is a significant positive relationship between high performance work practices and performance. However, the majority of the studies used organization-dominated performance measures, notably financial-economic indicators such as return on average assets, return on equity, turnover, sales, labor productivity and profitability. Therefore, less attention has been paid to exploring the concept of performance from an employeeâ€™s perspective. Using a resource-based view of the organization, organizations can simply develop sustained competitive advantage by generating value in a unique way through employees, which is difficult for competitors to replicate. Thus, itÂ is proposed that academics and practitioners should explore how organizations can develop sustained competitive advantage by keeping their employees engaged with their roles and organization. This paper explores high performance work practices and employee engagement in the selected higher educational institutions. This paper employs qualitative case study methodology. Data were gathered from two case studies and observation on high performance work practices and employee engagement. The research thus provides evidences on the high performance work practices that can keep the employees engaged.Â Â Â